Virulence of Rhynchosporium commune isolates collected in Iceland - Novakazi, Fluturë; Göransson, Magnus; Stefánsson, Tryggvi Sturla; Jalli, Marja; Hallsson, Jón Hallsteinn (Journal of Plant Pathology, 2021)
Abstract Various fungal species continue to be one of the most difficult challenges faced by farmers, and hence societies in whole, when it comes to securing plentiful and wholesome food for a rapidly growing human population. Understanding the biology of pathogenic fungi in detail, both at the population and molecular levels, combined with continued emphasis on resistance breeding of important crops, offers the most obvious sustainable solution to this pressing problem. Here we present results of virulence testing and microsatellite analysis on a collection of Icelandic Rynchosporium commune isolates to test whether the previously demonstrated genetic diversity observed translated into functional diversity in the virulence of these isolates. Our results show considerable diversity in the virulence of the Icelandic R. commune samples with each isolate having a unique virulence spectrum on the 15 near-isogenic barley lines used for screening. Our findings have practical implications, showing that even with short continuous barley cultivation and isolation by geographical distance, breeding for Icelandic, and likely other remote or isolated locations, still needs to consider the importance of disease resistance in breeding decisions and variation in local pathotypes. Moreover, our analysis is the first step to focused breeding for disease resistance for Icelandic conditions, an important step in the ongoing Icelandic barley breeding project.